2022
DOI: 10.3390/biomedicines10102669
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular Abnormalities and Systemic Arterial Stiffness Are the First Manifestation of Cardiovascular Abnormalities in Patients with Untreated Moderate to Severe Obstructive Sleep Apnoea and with Low to Intermediate Cardiovascular Risk—A Pilot Study

Abstract: This study aimed to investigate macro- and microvascular function parameters and their relationship with known markers of cardiovascular risk in patients with untreated moderate to severe obstructive sleep apnoea (OSA). Fourteen patients with moderate to severe OSA and fourteen controls were included in the present study. General assessments included BMI, systemic blood pressure (BP) and circulating markers for oxidative stress and endothelial function. Additional assessments included 24 h BP and heart rate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Exclusion criteria were family history of DM, a positive diagnosis of cardio- or cerebro-vascular disease, (coronary artery disease, heart failure, arrhythmia, stroke, transient ischaemic attacks), peripheral vascular disease, severe dyslipidaemia (defined as plasma TG > 6.00 mmol/L or cholesterol levels > 7.00 mmol/L), diabetes, as well as other metabolic disorders or chronic diseases that required treatment [ 9 , 19 , 20 ]…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were family history of DM, a positive diagnosis of cardio- or cerebro-vascular disease, (coronary artery disease, heart failure, arrhythmia, stroke, transient ischaemic attacks), peripheral vascular disease, severe dyslipidaemia (defined as plasma TG > 6.00 mmol/L or cholesterol levels > 7.00 mmol/L), diabetes, as well as other metabolic disorders or chronic diseases that required treatment [ 9 , 19 , 20 ]…”
Section: Methodsmentioning
confidence: 99%
“…When undergoing DVA analysis, individuals with untreated moderate-to-severe obstructive sleep apnea but without overt cardiovascular disease exhibited delayed reaction time in response to flicker, as well as decreased dilation amplitude, dilation slope, and postflicker constriction, which can be early indicators for future vascular complications [79]. However, continuous positive airway pressure (CPAP) withdrawal did not affect retinal vascular responses to flickering light, suggesting that there are different effects on macrovascular and microvascular endothelial function [80].…”
Section: Automated Retinal Vessel Analysis In Other General Conditionsmentioning
confidence: 99%
“…The analysis indicated that anticoagulation therapy was linked to a reduced risk of stroke, but it also carried a higher risk of major bleeding. This underscores the importance of adopting a personalized approach that takes into account individual risk factors [ 51 ]. In a similar vein, a comprehensive review was conducted to examine the effectiveness and safety of antithrombotic treatments, such as anticoagulants and antiplatelet agents, in patients with heart failure, both with and without atrial fibrillation.…”
Section: Reviewmentioning
confidence: 99%